eLingua : Issue 2 : July 2014 / Academy of Language Studies - Razali, Wan Noorli; Mohd Amin, Noraziah; Team, eLingua; Aboo Bakar, Rofiza; Yih, Mah Boon; Muhamad, Sabariah; Giap, Lim Soo (Academy of Language Studies, 2014)
1. UPALSICL 2 Luncheon 2. Publishing Informative Package for Teenagers’ Books Workshop 3. 3rd International Conference on Humanity, History and Society (ICHHS) 2014 4. Examination Template In-house Training 5. Workshop on ELC Textbook Usage 6. TEC and LIC workshop on Test-bank items 7. The Digital Storytelling Experience with the BEL311 Students 8. Web-based Cognitive Writing Instruction (WeCWI) 9. PROGRAM LAWATAN HOMESTAY -NANZAN UNIVERSITI JEPUN DI MENGKUANG TITI, P.PINANG 10. JAPAN EDUCATION FAIR 2014 11. PENGARUH WARNA DALAM KEHIDUPAN KAUM CINA